2014
DOI: 10.1097/ftd.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Trough Concentration Over 12.1 mg/L is a Major Risk Factor of Vancomycin-Related Nephrotoxicity in Patients With Therapeutic Drug Monitoring

Abstract: Vancomycin trough concentrations over 12.1 mg/L were associated with an increased risk of nephrotoxicity. This is lower than the known threshold. Trough vancomycin concentration over the threshold was the only risk factor of nephrotoxicity among demographic factors, dosing regimen, and other clinical conditions in this study. It is suggested that vancomycin trough concentrations greater than 12.1 mg/L require close monitoring for nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…It has been demonstrated that an initial trough concentration of vancomycin of ≥15 mg/l and a duration of therapy of ≥14 days are independent risk factors associated with higher rates of nephrotoxicity (27)(28)(29). A retrospective study including 1,269 cases reported that trough concentrations of >12.1 mg/l were a major risk factor for vancomycin-induced nephrotoxicity (30). In the present study, the threshold vancomycin trough and peak concentrations for nephrotoxicity were determined to be 16.08 and 30.42 mg/l, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that an initial trough concentration of vancomycin of ≥15 mg/l and a duration of therapy of ≥14 days are independent risk factors associated with higher rates of nephrotoxicity (27)(28)(29). A retrospective study including 1,269 cases reported that trough concentrations of >12.1 mg/l were a major risk factor for vancomycin-induced nephrotoxicity (30). In the present study, the threshold vancomycin trough and peak concentrations for nephrotoxicity were determined to be 16.08 and 30.42 mg/l, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Han et al also reported that a trough concentration over 12.1 mg/l was a major risk factor for nephrotoxicity in patients undergoing therapeutic vancomycin monitoring. 26 The nephrotoxicity might also be a particular matter in high-dose vancomycin therapy for MRSA infections. [27][28][29] Obviously, regular monitoring of vancomycin dosing is critical for the prevention of nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The association between VT or vancomycin total daily dose and AKI has been described in several studies [4,5,[8][9][10][11][12][13][14] . However, some studies demonstrated that higher VT level of 15-20 is not more associated with AKI than lower levels [7,15,16] .…”
Section: Discussionmentioning
confidence: 99%